Decision analysis considering the resilience level of the food supply chain under the risk of demand disruption - Liu, Jianyu; Kang, Kai; Lu, Lin; Dong, Ruihai; Luo, Xiaochun; Li, Chaoling; Long, Ping; Yang, Xiangjun; Mao, Siyi (Frontiers in Sustainable Food Systems, 2025)
In the context of demand disruption, food supply chain resilience not only helps enterprises maintain stability in the face of uncertainty and risk but also enables them to better satisfy customer demand, reduce costs, enhance competitiveness, and promote sustainable development. In order to analyze the resilient input and coordination of the food supply chain under the risk of demand disruption. This paper uses game theory as the methodological basis of the research to construct a game model between manufacturers and retailers. This model considers the impact of different demand interruption risks and product order quantities on food supply chain resilience input, manufacturer profits, and retailer profits. And analyzed the coordination mechanism of cost sharing contracts and revenue sharing contracts on the food supply chain. The results show that, under the risk of demand disruption, the cost-sharing contract is more suitable than the benefit-sharing contract for harmonizing the profits of food supply chain parties. Furthermore, the manufacturer's profit is negatively related to the probability of demand disruption, while the retailer's profit is positively related to this probability when the product order quantity is low, but negatively related when the product order quantity is high. food supply chain resilience input are positively correlated with the probability of demand disruption. Furthermore, during sensitivity analysis, the profits of both the manufacturer and retailer exhibit a U-shaped fluctuation, initially decreasing and then increasing, as the capacity restoration factor grows.